Indigenous Coaches and the National Aboriginal Hockey Championships - Hauck, Dallas Gerald (Scholarship@Western, 2020)
This thesis explores the National Aboriginal Hockey Championships (NAHC), an annual hockey tournament held in Canada where Indigenous youth compete in provincial/territorial teams. Research focused especially on the insights that coaches, organizers, and other tournament officials can provide into this tournament that aims to both highlight the skills of Indigenous players and also to provide cultural activities and enhance pride. Drawing on interviews at the NAHC at the 2019 tournament in Whitehorse, Yukon, Canada, this thesis aims to understand the impact the tournament has on those involved, as well as outside influences that constrain and impact the event. The major topics presented are history of the championships, experiences with coaching, and the role Indigenous identity plays. The influence of settler colonialism connects the different topics studied, and continues to impact Indigenous sport, in this case Indigenous hockey and its coaches, from systemic racism to skepticism about identity.